Perbandingan Niat Berwirausaha dan Belajar Mahasiswa di Perguruan Tinggi Kota Malang - Ahmad Nizar Yogatama (JMK (Jurnal Manajemen dan Kewirausahaan), 2019)
The number of educated unemployed in Indonesia is an initial phenomenon about the importance of entrepreneurship. Improvement of entrepreneurship is then carried out by universities, especially in Malang, through entrepreneurship-based courses, but there is a gap between theory and practice. The gap occurs because of differences in interest among students who are more inclined to entrepreneurship and study in higher education. The purpose of this study was to see differences in interest in entrepreneurship and interest in studying in college. The data analysis method used is partial least square with the student population of several public and private universities in the city of Malang. The results of the study show that the theory of planned behavior does not have a positive and significant effect on the intention to entrepreneurship, while the theory of planned behavior has a positive and significant effect on the intention to study in Higher Education.